350 Years of Jihad Fii Sabilillah Against the Colonizers: The Resistance of Sundanese Muslims Against the Colonizers: 350 Tahun Jihad Fii Sabilillah Melawan Penjajah: Perlawanan Umat Islam Tatar Sunda Melawan Penjajah - Dhaiman, Arif Noor; Wirahadi, Wirahadi (Civilization Research: Journal of Islamic Studies, 2024)
The purpose of this research is to find 350 years of jihad fii sabilillah of Sundanese Muslims against the colonizers. This research uses a historiographic approach by using descriptive analysis methods, interviews, observations and is complemented by library research using books, journals and other related literature. Based on the results of the research, mat Islam in the archipelago was never colonized for 350 years, but Muslims in the archipelago for 350 years fii Sabilillah jihad against European pagan colonialism. The figures who fought included Fatahillah, Sultan Agung Hanyokrokusumo, Sultan Ageng Tirtayasa, Syaikh Abdul Muhyi Pamijahan, Haji Raden Alit Prawatasari, Kyai Tapa, Ki Bagus Rangin, Syaikh Arsyad Thawil, KH. Wasyid, Pitung, Entong Gendut, the resistance of the Cirebon sultanate and the Menak politics of Cianjur, Sumedang, Limbangan and resistance through organizations to the Resistance of the Uthmaniyyah Consulate in Batavia which began in the era of Caliph Abdul Hamid II until the era of Caliph Muhammad V (1883 - 1924 AD).